The Effect of Citicoline on Electroretinography Abnormalities in Patients with Non-proliferative Diabetic Retinopathy - Anna Nur Utami; Elvioza Elvioza; M Sidik (Indonesian Vitreoretinal Society, 2019)
Introduction : to determine the effect of citicoline 1000 mg oral supplementation given for 4 weeks on electroretinography abnormalities in patients with NPDR (non-proliferative diabetic retinopathy). Methods : prospective, double blind, randomized clinical trial. Thirty-eight patients who matched the inclusion and exclusion criteria were randomized into two groups: the placebo (P-NPDR) and citicoline (C-NPDR). In the end, there were 18 eyes in citicoline group and 16 eyes in placebo group. The primary outcome was P50 and N95 amplitude in PERG within group and intergroup which were taken at the baseline and 4 weeks after treatment. Results : at the end of treatment, the N95 amplitude in C-NPDR showed improvement, 4.85 (1.9-10.3) µV, before treatment to 5.7 (1.9-17.1) µV, after treatment with P = 0.04. Median P50 amplitude improved in both groups, with C-NPDR: 3.1 µV to 3.8 µV (p = 0.89), and P-NPDR: 3.5 µV, to 4.5 µV (p = 0.10). Delta ∆N95 amplitude is higher in C-NPDR, while delta ∆P50 amplitude is higher in P-NPDR, with P values 0.35 and 0.45. Conclusion : Oral citicoline may induce a significant improvement in mean N95 amplitude before and after the treatment. P-NPDR showed positive trend in P50 amplitude while in C-NPDR showed positive trend in N95 amplitude, but these values were not statistically significant (P = 0.45; P= 0.35).